Relevansi Taubat dengan Kesehatan Mental dalam Islam - Reva Husniati; Cucu Setiawan; Dian Siti Nurjanah (Jurnal Penelitian Ilmu Ushuluddin, 2023)
The purpose of this study is to reveal: 1) The concept of repentance according to Sufism (the Sufis) and psychology; 2) The concept of mental health according to western psychology and Sufism; and 3) The relevance of repentance to mental health according to Islam. This research belongs to the type of research (library research), using descriptive qualitative methods, and western psychological theory and the concept of repentance according to the Sufis as a knife of analysis. The findings in this study are: First, repentance according to the Sufis must be carried out solely for the sake of Allah and is determined to leave sins that have been committed in the past and not to repeat them. While repentance in the psychological view is defined as a person's encouragement to always fill himself with positive things and behaviors that direct him to foster peace of mind. Second, mental health in psychology is a psychological condition of a person in adjusting himself to his problems, whether it is within himself or outside himself by showing his abilities. Meanwhile, in Sufism's view, mental health is an ability to control mental functions, so that a good adjustment will be created, between oneself, other people, the environment, the universe or with God. Third, the relevance of repentance and mental health in Islam is the result of the process of cleansing the soul, so a mentally healthy person is a person whose soul is clean. The relationship between mental health and repentance in Islam cannot be separated, because the steps to achieve health can be produced through repentance. Repentance and mental health come from religious teachings. If the two are combined well, they can form a perfect soul, in other words, they can give birth to human beings.